Depressive Symptoms as a Predictor Factor of All-Cause Mortality within Six Months in Elderly Hemodialysis Patients - Perdhana, Langgeng; Chasan, Shofa; Mupangati, Yudo Murti; Nuraini, Siti (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Depression is a mental disorder that is often found in the elderly and hemodialysis patients, resulting in bad effects on patients. There is no study on the relationship between depression and all-cause mortality risk in elderly hemodialysis patients in Indonesia. This study aimed to determine the role of depression as a predictor factor of all-cause mortality within 6 months in elderly hemodialysis patients. Methods. A prospective cohort study was conducted from February to August 2020 at the hemodialysis unit of Roemani Muhammadiyah Hospital, Semarang. The inclusion criteria were elderly patients (aged ≥60 years), undergoing hemodialysis ≥3 months, hemodialysis frequency twice a week, willing to participate in this study, able to communicate well, and has no history of mental disorders include a history of psychotic disorders and mental disorders due to substance use. Meanwhile, patients whose data were incomplete, transferred to another hemodialysis unit, HBsAg +, hemoglobin level /dl. FRAILTY score >2, and had other stressors not related to hemodialysis or chronic kidney disease (CKD) such as social, family, and work factors were excluded from this study. Depression was assessed using the Beck Depression Inventory-II questionnaire. The collected data was then analyzed using Kaplan Meier and Cox Regression.Results. Of 32 respondents, most of them were male (81.3%). The mean age was 67.2 (SD 7) years. There were 6 (18.7%) respondents categorized into a depression group and 26 (81.3%) respondents into a non-depression group. Cox Regression analysis showed that depression was a predicting factor of all-cause mortality within six months in elderly hemodialysis patients (p value=0.012, and Hazard ratio=10.149). Conclusion. Depression is a predictor factor of all-cause mortality within six months in elderly hemodialysis patients.